Increased alveolar nitric oxide concentration and high levels of leukotriene B(4) and 8‐isoprostane in exhaled breath condensate in patients with asbestosis - Lehtonen, Hannele (BMJ Group, 2007)
BACKGROUND: Inhaled asbestos fibres can cause inflammation and fibrosis in the lungs called asbestosis. However, there are no non‐invasive means to assess and follow the severity of the inflammation. Exhaled nitric oxide (NO) measured at multiple exhalation flow rates can be used to assess the alveolar NO concentration and bronchial NO flux, which reflect inflammation in the lung parenchyma and airways, respectively. The aim of the present study was to investigate whether exhaled NO or markers in exhaled breath condensate could be used to assess inflammation in asbestosis. METHODS: Exhaled NO and inflammatory markers (leukotriene B(4) and 8‐isoprostane) in exhaled breath condensate were measured in 15 non‐smoking patients with asbestosis and in 15 healthy controls. Exhaled NO concentrations were measured at four constant exhalation flow rates (50, 100, 200 and 300 ml/s) and alveolar NO concentration and bronchial NO flux were calculated according to the linear model of pulmonary NO dynamics. RESULTS: The mean (SE) alveolar NO concentration was significantly higher in patients with asbestosis than in controls (3.2 (0.4) vs 2.0 (0.2) ppb, p = 0.008). There was no difference in bronchial NO flux (0.9 (0.1) vs 0.9 (0.1) nl/s, p = 0.93) or NO concentration measured at ATS standard flow rate of 50 ml/s (20.0 (2.0) vs 19.7 (1.8) ppb, p = 0.89). Patients with asbestosis had increased levels of leukotriene B4 (39.5 (6.0) vs 15.4 (2.9) pg/ml, p = 0.002) and 8‐isoprostane (33.5 (9.6) vs 11.9 (2.8) pg/ml, p = 0.048) in exhaled breath condensate and raised serum levels of C‐reactive protein (2.3 (0.3) vs 1.1 (0.2) μg/ml, p = 0.003), interleukin‐6 (3.5 (0.5) vs 1.7 (0.4) pg/ml, p = 0.007) and myeloperoxidase (356 (48) vs 240 (20) ng/ml, p = 0.034) compared with healthy controls. CONCLUSIONS: Patients with asbestosis have an increased alveolar NO concentration and high levels of leukotriene B4 and 8‐isoprostane in exhaled breath. Measurement of exhaled NO at multiple exhalation flow rates and analysis of inflammatory markers in exhaled breath condensate are promising non‐invasive means for assessing inflammation in patients with asbestosis.